The happy manifesto : make your organization a great workplace - Stewart, Henry, 1959- (London : Kogan Page, 2012)
Imagine a workplace where people are energized and motivated by being in control of the work they do. Imagine they are trusted and given freedom, within clear guidelines, to decide how to achieve their results. Imagine they are able to get the life balance they want. Imagine they are valued according to the work they do, rather than the number of hours they spend at their desk. Wouldn't you want to work there? Wouldn't it also be the place that would enable you to work at your best and most productive? The Happy Manifesto is a guide to anyone wanting to improve their workplace. Learn how you too could change your work environment for the better.
Keywords: Corporate culture; Employee motivation; Job satisfaction; Work environment